Ectopic fat: causes, consequences and treatment - Smith, Steven (Henry Stewart Talks, 2009)
Definition of ectopic fat, Consequences of ectopic fat, Insulin resistance, Beta cell failure, Increased VLDC cholesterol production / atherogenic dyslipidemia, Adipose tissue dysfunction, Adipose tissue inflammation, An inadequate number of fat cells compared to the energy 'burden', Large fat cells, insulin resistance, Transgenic animal models, Visceral fat is the 'other' ectopic adipose tissue, Adipose tissue is a complex organ, there is still room for discovery at many levels, Waist circumference, Abdominal adipose tissue; nomenclature, Subcutaneous adipose tissue: radiographic considerations, The study of muscle mitochondria, Pre-clinical models, Modest weight loss reverses ectopic fat, Exercise vs. weight loss, Treatment, TZD's and ectopic lipid